Biopanning For Peptides That Interact With 2, 4-Dichlorophenoxyacetic Acid And Their Detection In The Medium Of Oil Palm Suspension Culture. - Md Aris, Nurwatti (2007)
2, 4- dichlorophenoxyacetic acid (2, 4-D) is one of the commonly used plant growth regulators in somatic embryogenesis of oil palm cultures. However, high concentrations of 2, 4- D have been associated with abnormalities deriving from these cultures. Therefore, to discern the optimal concentration of 2, 4-D that can be safely used in oil palm tissue culture, a phage-ELISA (Enzyme Linked Immunosorbent Assay) was developed. Biopanning was carried out for four rounds, by incubating a pool of disulfide constrained phage displayed peptide library with 2, 4-D that had been immobilized onto a microtiter plate. The unbound phages were washed away while the bound phages were eluted and amplified in Escherichia coli. The ssDNAs of phages from the 3rd and 4th rounds of biopanning were extracted and sequenced. Two phages bearing the C-TQANRLT-C and C-IPGKPFY-C sequences interacted with 2, 4-D in ELISA. A capture dot blot assay, which applys colorimetry in the detection of 2, 4-D, was established and the peptide C-IPGKPFY-C gave a better colour formation compared to C-TQANRLT-C peptide. The intensity of the colour formed is indicative of the binding capacity of the peptide. The phages were used as capturing antigens for the development of the phage-ELISA and the sensitivity of the assay was 1-10 ng/ml. The selected peptides were used for detecting 2, 4-D in actual Murashige & Skoog (MS) liquid medium containing oil palm suspension culture. Difference in absorbance value in the positive and negative culture was only shown in the media that have been centrifuged at 5000 rpm. The C-IPGKPFY-C phage was found to cross react with thiamine molecule that has similar aromatic ring structure with 2, 4-D, in the suspension culture.